2017
DOI: 10.1175/jhm-d-17-0139.1
|View full text |Cite
|
Sign up to set email alerts
|

Validation of IMERG Precipitation in Africa

Abstract: Understanding of hydroclimatic processes in Africa has been hindered by the lack of in situ precipitation measurements. Satellite-based observations, in particular, the TRMM Multisatellite Precipitation Analysis (TMPA) have been pivotal to filling this void. The recently released Integrated Multisatellite Retrievals for GPM (IMERG) project aims to continue the legacy of its predecessor, TMPA, and provide higher-resolution data. Here, IMERG-V04A precipitation data are validated using in situ observations from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
74
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 38 publications
1
74
0
1
Order By: Relevance
“…Mayor et al () concluded that IMERG performed fairly well but still had a 2‐hr lag in the peak time in the countrywide mean diurnal cycle over Mexico. By using six gauge stations in Africa, Dezfuli et al () also proved the improved performance of IMERG in terms of diurnal cycle. However, to varying degrees, these studies were limited by factors such as data sources or research period and thus revealed only a few aspects of the diurnal characteristics.…”
Section: Introductionmentioning
confidence: 92%
“…Mayor et al () concluded that IMERG performed fairly well but still had a 2‐hr lag in the peak time in the countrywide mean diurnal cycle over Mexico. By using six gauge stations in Africa, Dezfuli et al () also proved the improved performance of IMERG in terms of diurnal cycle. However, to varying degrees, these studies were limited by factors such as data sources or research period and thus revealed only a few aspects of the diurnal characteristics.…”
Section: Introductionmentioning
confidence: 92%
“…The satellite/gridded data produce the area average of precipitation in contrast with point measurements obtained with rain gauges. Earlier studies have shown that diverse altitude and geographic and climate conditions have greatly impact on the accuracy and performance of satellite or other precipitation products [2,[5][6][7][8][9][10][11]. For instance, in a study by Gottschalck et al [12] the overestimation of 3B42-RT over the Central United States is attributed to misclassification of cold cirrus clouds as precipitating systems.…”
Section: Introductionmentioning
confidence: 99%
“…After improvements in IMERG-V03, the NASA Goddard Space Flight Center (GSFC) introduced Version 04 (V04) of IMERG on March 22, 2017. Likewise V03, precipitation estimates from the IMERG-V04 were also assessed worldwide and the uncertainties and errors in the precipitation retrieval algorithms were identified over the diverse landscapes and climate systems [4,[33][34][35][36][37]. After modification in the precipitation retrieval algorithm of IMERG-V04, the version 5 (V05) was launched on November 20, 2017.…”
Section: Introductionmentioning
confidence: 99%